P35 A RARE CASE OF VENTRICULAR ARRHYTHMIA STORM AND COMPLETE ATRIOVENTRICULAR BLOCK IN A PATIENT WITH BECKER MUSCULAR DYSTROPHY. (18th May 2022) - Zannoni, J; Del Torto, A; Tundo, F; Assanelli, E
Abstract: A 68 year–old male presented to the Emergency Department of our Institute with palpitations for the last 20 minutes. The patient suffered from Becker's muscular dystrophy (BMD) with hypotonic tetraparesis and dilated cardiomyopathy with moderate left ventricular dysfunction. The patient had also arterial hypertension and a previous ischemic stroke treated with thrombolysis and subsequently with warfarin. On the admission, the patient was alert, blood pressure was 90/60 mmHg and heart rate 180 bpm. An ECG (Fig. 1 ) showed regular, wide–complex tachycardia (QRS duration of 240 msec) with right branch block morphology with left axial deviation. A bolus of amiodarone 200 mg ev was administered without efficacy followed by a bolus of lidocaine 50 mg. The patient developed symptomatic hypotension, so external electrical cardioversion was performed with a single DC shock at 200J, effective in restoring sinus rhythm. Amiodarone and beta blocker therapy was started. On laboratory tests, the main values were normal, including the ultrasensitive troponin hs–cTnI. Echocardiography showed a mildly dilated left ventricle with diffuse hypokinesia conditioning severe reduction of systolic function (FE 35%) (Fig. 2 ). On subsequent telemetric ECG monitoring, no recurrences of sustained ventricular tachycardia (VT) were recorded, but it was observed an episode of complete atrioventricular (AV) block conditioning a symptomatic 9.5–second asystole, treated with atropine. Then the patient underwent CRT–D implantation in secondary prevention. The day after the procedure, an arrhythmic storm occurred and was effectively treated with multiple attempts of antitachycardia pacing and device shock. In the following days, the patient continued to present with episodes of VT despite antiarrhythmic drugs. Hence, an endo–epicardial ablation of the arrhythmic substrate was evaluated in Heart team. In view of an intubation and the high anesthesiological risk, it was indicated to continue the optimized medical therapy. Mexiletine 200 mg tid was added to metoprolol 100 mg bid and amiodarone 200 mg od. In the following days, no arrhythmic recurrences were recorded on continuous ECG monitoring. The patient was discharged from the hospital asymptomatic and with no sign of heart failure. At 2 years of follow–up, the patient remained asymptomatic, with no arrhythmic events recorded by the device and in the absence of any adverse effects caused by mexiletine.